Strategi Membangun Merek Toyota dalam Menghadapi Tantangan dan peluang di Industri Otomotif. - Millen Kaur; Daniel Vieri; Mohamad Zein Saleh (Fakultas Ekonomi & Bisnis, Universitas Nusa Nipa, 2024)
This study aims to understand the strategies implemented by Toyota in building its brand and how these strategies address challenges and opportunities in the automotive industry. A qualitative approach with a literature review research methodology is employed to explore this phenomenon.The philosophy of postpositivism serves as the philosophical foundation of this study, acknowledging that research is influenced by the researcher's subjective perspective and efforts are made to address biases through rigorous methodological approaches.Through data collection from various relevant literature sources, including journal articles, books, industry reports, and other electronic sources, this study analyzes marketing strategies, product innovations, and adaptations to environmental changes that have been implemented by Toyota.Qualitative data analysis yields a deep understanding of how Toyota builds its brand, responds to market changes, and faces competition in the automotive industry. The findings of this study provide valuable insights for Toyota and other stakeholders in the automotive industry in formulating effective strategies to maintain and enhance their positions in the competitive market.